2017
DOI: 10.21475/ajcs.17.11.10.pne645
|View full text |Cite
|
Sign up to set email alerts
|

Application of different cover crops and mineral fertilizer doses for no-till cultivation of broccoli, cauliflower and cabbage

Abstract: No-till practices have not been widely adopted by vegetable producers due to the necessity of seedbed preparation to incorporate organic fertilizers and plant residues of the preceding crops. This study evaluated biomass yield and residue decomposition of different cover crops, and their influence on agronomic performance of Brassica crops cultivated under no-till system. The experiment was laid out in randomized complete blocks with 4 x 3 factorial treatment combinations of four cover crops: Sunn hemp (SH), S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…The production of DM by the soil coverages studied are above the averages observed in other studies also conducted in the Brazilian Cerrado biome, ranging from 7 to 12 Mg ha -1 for C. juncea (Torres et al, 2017), 3.8 to 7.2 Mg ha -1 for C. ensiformis (Padovan et al, 2011;Torres et al, 2014) and from 2 to 7.2 Mg ha -1 for the fallow area (Crusciol & Soratto, 2009). The great biomass production observed in this study is probably due to the adequate water availability and temperature that occurred in the region during the study period.…”
Section: Resultssupporting
confidence: 49%
“…The production of DM by the soil coverages studied are above the averages observed in other studies also conducted in the Brazilian Cerrado biome, ranging from 7 to 12 Mg ha -1 for C. juncea (Torres et al, 2017), 3.8 to 7.2 Mg ha -1 for C. ensiformis (Padovan et al, 2011;Torres et al, 2014) and from 2 to 7.2 Mg ha -1 for the fallow area (Crusciol & Soratto, 2009). The great biomass production observed in this study is probably due to the adequate water availability and temperature that occurred in the region during the study period.…”
Section: Resultssupporting
confidence: 49%
“…In their studies, Assis et al (2016) and Torres et al (2017) observed similar results when using brachiaria, since the rate of decomposition of the brachiaria residues were accelerated when compared to crotalaria and millet, suggesting that it is not only the C/N ratio of plant residues to decisively affect the process of plant residue decomposition. The C/N that these plants feature in monoculture, when compared with cover crop mixtures, may present middle or higher ratios of decomposition, as evidenced in other studies carried out in the same region (Torres et al, 2013;Assis et al, 2016;Pacheco et al, 2013).…”
Section: Discussmentioning
confidence: 80%
“…Some other studies evaluating the decomposition of residues of millet, sunn hemp and brachiaria in natural conditions (no artificial irrigation) showed that the greatest rates of decomposition always occur on Fabaceae, and minor in Poaceae (Carvalho et al, 2011;Assis et al 2016;Torres et al, 2015Torres et al, , 2017. These authors also observed that the rates are directly influenced by soil moisture because the decomposition increases in parallel to the increase of water availability that occurs in the rainy period and decrease to minimum values in the dry period (Torres et al, 2008;Pacheco et al, 2017).…”
Section: Discussmentioning
confidence: 93%
“…Similarly, Rosen et al [15] found that the application of 250 kg ha −1 N increased the cabbage yield by 17% compared to a low nitrogen rate of 125 kg ha −1 N. In another study, Cui et al [7] reported that the application of the inorganic fertilizer N-P-K (15-6.5-12.4) increased the cabbage yield by 18.3% compared to a control treatment in which no N was applied, and the combined application of inorganic fertilizer with organic fertilizer further increased the crop yield. In an experiment conducted in Brazil, the application of 150 kg ha −1 N, 100 kg ha −1 P 2 O 5 and 100 kg ha −1 K 2 O increased the cabbage yield by 45.6% compared to the control treatment [16].…”
Section: Introductionmentioning
confidence: 96%